Graphene-Based Nanomaterial and Its Applications as Drug Nanocarrier - Sun, Yucong (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Graphene-based nanomaterial can be used in many fields due to its excellent properties. Nowadays, it is widely used in drug delivery systems as nanocarriers due to its unique structure, large surface area, and biocompatibility. It can be more easily combined with other nanoparticles through modification. Cancer is a disease with a high mortality rate. It remains the top rank leading to death for many years. In order to treat cancer, using graphene and its derivatives as nanocarriers to transport medicine has become a popular strategy in recent years. In this review, several features of graphene-based nanomaterials were discussed firstly, which is the reason why graphene can be used as material carriers. Then, the functionalization of graphene materials using both covalent and non covalent methods was emphasized. Besides, specific examples of graphene as nano anti-cancer carriers were introduced. Moreover, the advantages and disadvantages of this kind of material were discussed. Finally, the potential research directions of graphene as a drug carrier in the future were discussed. This work will contribute to promoting the application of graphene based nanomaterials as drug nanocarriers.